Stochastic scheduling of ground movement problem integrated with taxiway routing and gate/stand allocation. Issue 9 (24th June 2022) - Yang, Yuanchao; Gao, Zichen
Abstract: The authors propose a new scheduling model and solution method for Ground Movement Problem (GMP) which is designed to manage the movements of flights on the surface of airport air‐side in an effective manner. Since the arrival time for arrival flights and off‐block time for departure flights are usually uncertain parameters for GMP, the proposed scheduling model is stochastic and integrates the three‐dimensional (3‐D) taxiway routes' assignment (with variable taxiing speed for flights) and the gates/stands allocation for the flights, with fully capturing multiple constraints related to taxiways, gates/stands and aircraft performance limits. The solution method also provides a stochastic quantification scheme concerning both uncertainties by the arrival time and off‐block time information. The schedule results can realize the immunity of the above time uncertainties within a tolerable risk probability. We finally provide numerical analysis to verify the stochastic scheduling model with mixed integer and linear programming (MILP) basics and illustrate the effectiveness of proposed solution method by a test case on Hangzhou international airport in China.